Challenging women : gender, culture, and organization - Maddock, Su (Sage, 1999)
This book offers a radical reassessment of organizational forces for change and barriers encountered by the c̀hallenging women' - senior women managers faced with the task of transforming their organizations. Much has been written about women at work, the g̀lass ceiling' and discriminatory employment practices. This study is seminal in the linkage it makes between gender, innovation and organizational transformation. The book highlights the implications of this for all types of organizations and women managers everywhere.